Comparative studies of the distribution of invertebrates found in exposed and protected rocky shores of Pulau Kapas, Terengganu - Mohd. Subri Haji Saadon (Fakulti Pengajian Maritim dan Sains Marin, 2011)
A quantitative survey was made on the communities on exposed and protected rocky shores of Pulau Kapas, Trengganu. The protected shores are gentle sloping while the exposed shores which experience direct Wave action, slopes steeply into the sea. Three zones are defined ; sublittoral, eulittoral and littoral fringe.